Observing children : a practical guide - Sharman, Carole. (Cassell, 2000)
This book is about: Why Do Observations? a Step-by-Step Guide to Presenting an Observation; Experimenting with Observational Techniques; Extending and Utilizing your Observations; Linking Observations and Assessments to the Desirable Outcomes for Learning; Activities to Promote Developmental progress; Developmental Milestones from Birth to 8 Years.